3D Numerical Modeling of Pile Group Responses to Excavation-Induced Stress Release in Silty Clay - Soomro, M. A.; Brohi, A. S.; Soomro, M. A.; Bangwar, D. K.; Bhatti, S. A. (Engineering, Technology & Applied Science Research, 2018)
Development of underground transportation systems consists of tunnels, basement construction excavations and cut and cover tunnels which may encounter existing pile groups during their construction. Since many previous studies mainly focus on the effects of excavations on single piles, settlement and load transfer mechanism of a pile group subjected to excavation-induced stress release are not well investigated and understood. To address these two issues, three-dimensional coupled-consolidation numerical analysis is conducted by using a hypoplastic model which takes small-strain stiffness into account. A non-linear pile group settlement was induced. This may be attributed to reduction of shaft resistance due to excavation induced stress release, the pile had to settle substantially to further mobilise end-bearing. Compared to the Sp of the pile group, induced settlement of the single pile is larger with similar settlement characteristics. Due to the additional settlement of the pile group, factor of safety for the pile group can be regarded as decreasing from 3.0 to 1.4, based on a displacement-based failure load criterion. Owing to non-uniform stress release, pile group tilted towards the excavation with value of 0.14%. Due to excavation-induced stress release and dragload, head load of rear piles was reduced and transferred to rear piles. This load transfer can increase the axial force in front piles by 94%.